CSR in Extractive Industries: Critical Analysis through Social Constructivism, Hegemony, and Political Ecology - Rahmatullah; Naping, Hamka; Safriadi (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Corporate Social Responsibility (CSR) in the extractive industry is often positioned as a form of corporate concern and an instrument of sustainable development. However, practices in the field are usually paradoxical: on the one hand, they provide social benefits, on the other, they accompany environmental damage and society's dependence on companies. This article critically examines CSR practices in Indonesia's mining sector by highlighting the case of PT Berau Coal in East Kalimantan. The research uses a critical literature review that combines three theoretical lenses: Berger & Luckmann's social constructivism, Gramsci's hegemony, and political ecology. The analysis shows that CSR is a contested socio-political arena: (1) CSR is built as a social reality through externalization-objectification-internalization to normalize the role of corporations; (2) CSR functions as a hegemonic strategy that builds legitimacy, creates consensus, and dampens resistance through symbolic-institutional co-optation; and (3) from a political ecology perspective, CSR tends to depoliticize environmental issues and reproduce ecological injustice. The article concludes that CSR needs to be understood as a governance culture technology that works at a symbolic, ideological, and ecological level. The article's contribution lies in offering a critical integrative framework for assessing CSR in Indonesia's extractive sector and recommending a reorientation towards a community-based participatory model that is environmentally just